Веб-сервіс із прогнозування процесів на фондовому ринку - Горохов Д. В. (My University, 2023)
Ця дипломна робота присвячена проектуванню та розробленню веб-сервісу з прогнозування процесів на фондовому ринку. Метою дипломної роботи є якісне прогнозування процесів на фондовому ринку на основі веб-сервісу з прогностичною моделлю для передбачення ціни акцій у короткостроковій перспективі на фондовому ринку. Об’єкт дослідження. Процеси ціноутворення фондового ринку. Предмет дослідження. Програмно-технічні, організаційні засади, принципи, підходи щодо побудови веб-сервісу з прогнозування процесів на фондовому ринку. Методи дослідження. Метод порівняння підходів операцій з фондовим ринком, емпіричний аналіз, моделювання програмної системи та аналіз літературних джерел і наукових статей.

This thesis is devoted to the design and development of a web service for forecasting processes on the stock market. The purpose of this thesis is to design and implement a web service with a predictive model for predicting stock prices in the short term on the stock market. To achieve this goal, the following tasks need to be solved analyze the main processes of the stock market and ways to automate them; analyze the ways to automate stock market processes; compare the available models for forecasting the short-term share price; to design, implement, and deploy a web service for forecasting processes on the stock market, taking into account requirements engineering; Object of research. Operations and pricing of the stock market. Subject of research. Software, technical, organizational principles, principles, approaches to building a web service for forecasting processes on the stock market. Research methods. Method of comparing approaches to stock market operations, empirical analysis, modeling of the software system and analysis of literary sources and scientific articles.
Keywords: машинне навчання; нейронні мережі; мікросервісна архітектура; фондовий ринок; Vue.js; Node.js; machine learning; neural networks; microservice architecture; stock market